The impact of Customer Relationship Marketing (CRM) on customer loyalty in Holiday Inn, Melaka / Rosmalawaty Abdul Malek and Fathiah Abd Rahman - Abdul Malek, Rosmalawaty; Abd Rahman, Fathiah (2015)
The title of this study is “The Impact of Customer Relationship Marketing ( CRM ) on Customer Loyalty in Holiday Inn, Melaka”. The first purpose of this study is to determine the current level of customer loyalty towards Holiday Inn, Melaka. There are five independent variables involved in this study which are Trust, Commitment, Communication, Empathetic and Reliable. In order to completing this study, the hypothesis was been constructed and focused on the objective to determine whether there has significant relationship between those independent variables with customer loyalty. A total of 150 peoples have participated in this study as respondents. The methodology used for the study was primary data collection. For primary data, the researcher was used the method of questionnaire to obtained through the analyzing and interpret data of result. The reliability test, regression, frequency analysis, descriptive testing and Pearson’s correlation coefficient testing was used for data analysis. From correlation testing, the result shows that two of the independent variables which are trust and reliable have a strong relationship with customer loyalty while relationship with other independent variables which are commitment, communication and empathetic are moderate relationship respectively. For hypothesis, there are clearly shown that all of the hypothesis including commitment, communication and empathetic are supported.